Estrategias metodológicas y su incidencia en el aprendizaje de las matemáticas en estudiantes de 2 año EGB de la Unidad Educativa Emigdio Esparza Moreno de la ciudad de Babahoyo, 2023 - Morán Barreiro, Gabriela Rocío (2023)
Methodological strategies are planned approaches and techniques that educators use with the purpose of facilitating the acquisition of knowledge and skills of students. These strategies constitute a set of pedagogical methods that seek to promote the understanding of concepts and theories in a more accessible and active way. by the student. For this reason, the main objective of this research is to determine the incidence of methodological strategies in the learning of mathematics in 2nd year EGB students of the Emigdio Esparza Moreno Educational Unit in the city of Babahoyo, 2023. The methodology used In the case study it follows a qualitative approach; While the research was descriptive, field and explanatory, inductive and deductive methods were also used, the population is represented by 35 students and as a sample 10 students with mathematics learning problems were selected, in addition the tutor teacher of the 2nd parallel year “A” belonging to the Emigdio Esparza Moreno Educational Unit, it is important to mention that to obtain relevant information on the topic, two techniques were used: direct observation, directed at the students, and an interview with the teacher was also used. The results obtained were that the teacher does not apply the necessary strategies to awaken interest in learning in this subject, the methodology used by the teacher lacks innovation and creativity; which considerably influences the learning process of 2nd year EGB students. Therefore, it is concluded that the strategies used do not allow adequate learning of mathematics.